REVIEW OF RESEARCH AND METHODS REGARDING THE DIAGNOSIS OF HIP IMPINGEMENT - Yazdifar, Mahshid; Yazdifar, Mohammadreza (European Scientific Journal, ESJ, 2015)
One of the main reasons for OA (Osteoarthritis) is hip impingement and surgery regarding this is one of the most common operations performed in sports medicine. The cost of such intervention is hard to evaluate because medical centres assert that details regarding their charges and costs are proprietary information. However, reports from one academic medical centre have indicated the cost of hip impingement surgery is less than that of THR (Total Hip Replacement) (Kolata, 2011) which may suggest that the early detection of FAI(Femoroacetabular Impingement) could reduce the cost burden of this form of surgery for the NHS. The mean time taken from the initial symptoms emerging to a final diagnosis of FAI is three years (Clohisy, Knaus and Hunt, 2009 ). Early diagnosis is very challenging since many FAI patients experience an insidious onset of symptoms that is similar to other muscle dysfunction related diseases. Many of them go through delays and incorrect diagnoses as well as treatment recommendations that are ineffective. but late diagnosis causes OA and damage to soft tissue. FAI occurs in young and active adults who need a full range of motion and so detection at an early stage is essential. Moreover, there is a pressing need to investigate a reliable, valid and easy to implement impingement detection framework. In this review paper there is a discussion of methods and research regarding detecting hip impingement along with a consideration of their limitations.